2021
DOI: 10.31219/osf.io/uqp8d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is left after an error? Towards a comprehensive account of goal-based binding and retrieval

Abstract: The cognitive system readily detects and corrects erroneous actions by establishing episodic bindings between representations of the acted upon stimuli and the intended correct response. If these stimuli are encountered again, they trigger the retrieval of the correct response. Thus, binding and retrieval efficiently pave the way for future success. The current study set out to define the role of the erroneous response itself and explicit feedback for the error during these processes of goal-based binding and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…We handled performance feedback similarly in the main study (see Stimuli and apparatus and Procedure ). Validating this design choice, we found similar effects of error cancellation in a replication study of the reported work, where we manipulated between participants whether the commission of an error was or was not fed back at the end of a trial (see electronic supplementary material, figure S1 for the trial procedure; [ 25 ]). Again, we found shorter RDs, F 1,92 = 62.20, p < 0.001, 0.40 , d z = 0.81, and shorter RTs, F 1,92 = 106.37, p < 0.001, 0.54 , d z = 1.06, for errors than for correct responses across feedback conditions (with non-significant main effects of feedback and two-way interactions of accuracy and feedback in RDs and RTs, F s 1,92 ≤ 1.52, p s ≥ 0.220, 0.02 , d z ≤ 0.13).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…We handled performance feedback similarly in the main study (see Stimuli and apparatus and Procedure ). Validating this design choice, we found similar effects of error cancellation in a replication study of the reported work, where we manipulated between participants whether the commission of an error was or was not fed back at the end of a trial (see electronic supplementary material, figure S1 for the trial procedure; [ 25 ]). Again, we found shorter RDs, F 1,92 = 62.20, p < 0.001, 0.40 , d z = 0.81, and shorter RTs, F 1,92 = 106.37, p < 0.001, 0.54 , d z = 1.06, for errors than for correct responses across feedback conditions (with non-significant main effects of feedback and two-way interactions of accuracy and feedback in RDs and RTs, F s 1,92 ≤ 1.52, p s ≥ 0.220, 0.02 , d z ≤ 0.13).…”
mentioning
confidence: 65%
“…The observation of immediate error cancellation also suggests that the erroneous action might be subject to inhibition. Instead, erroneous responses seem to remain even more accessible in an upcoming action episode compared with a neutral response that neither corresponded with the preceding erroneous nor the actual correct response ([ 25 ]; see also [ 44 , 45 ]). This observation, however, does not contradict the assumption of an overall inhibition of motor activity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous research focused on cognitive control in challenging, but correct trials, the current study extends the notion of binding and retrieval of control states to erroneous actions. Theoretical accounts consider errors as a special case of conflict – while conflict during correct trials should be highest before response execution (i.e., before the correct response is selected amongst other highly active but inappropriate responses), conflict in trials with incorrect responses should be highest during and after response execution, because of the concurrent activation of the incorrect and the correct response ( Foerster et al, submitted ; Yeung et al, 2004 ). Despite these differences, errors should yield strong control states at least by the end of a behavioral episode.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical accounts have further proposed that only correct actions are subject to binding ( Hommel, 2005 ), yet, recent evidence suggests a different picture. Binding of stimulus and response features does indeed take place for action slips, with the correct but not executed response being bound to task-relevant and task-irrelevant stimulus features during error commission ( Foerster et al, submitted ; Foerster, Moeller, et al, 2021 ; Foerster, Rothermund, et al, 2021 ). Features of the executed erroneous response still remain activated and can enter bindings with action-triggered changes in the agent’s environment.…”
Section: Introductionmentioning
confidence: 99%